MSMEs RATTAN BUSINESS MODEL IN PULANG PISAU REGENCY IN SUPPORTING SUSTAINABLE MANAGEMENT OF PEATLAND ECOSYSTEMS - Widyastutik; Deden Djaenudin; Sahara (School of Business, IPB University (SB-IPB), 2021)
In supporting the sustainable management of the peat ecosystem, the participation of the community around the peat ecosystem is needed. The challenge faced is how to encourage local communities with sustainable peatland-based economic activities. Rattan is one of the paludicultural commodities that is endemic to habitat that can grow on peatlands and has economic potential and even export orientation. This study aims to [1] analyze the development of a rattan handicraft business model in peatlands [2] Evaluation of the rattan handicraft business on peatlands. The types of data used in this study are primary and secondary. Secondary data were obtained through interviews and FGDs with respondents of MSMEs Rattan in Gohong, Garung and Pilang Villages, Pulang Pisau Regency, and related agencies. The analytical method used is the business model canvas (Business Model Canvas) and the NPV business valuation, IRR, BC Ratio and Payback Period. Based on the analysis, 9 elements of the canvas business were identified as several critical points in the existing canvas business model of rattan MSMEs in Pulang Pisau Regency. Some of these critical points include: [a] technical aspects of improving skills, especially making up to date rattan handicraft designs which still need guidance, [c] access and market reach that are still not broad, (d) difficulties in access to banks (e) constraints on export procedures, (f) ability to do branding. Business valuation shows a positive Net Present Value which indicates that this business has a significant economic impact with a high positive value. IRR has a value greater than the rate of return, Net B / C above 1 and a payback period that is less than the life of the project (assuming the project life is 5 years). Keywords: business model canvas, business valuation, rattan MSMEs, peat